The Role of Glial Cells in the Pathophysiology of Epilepsy - Filiz Onat; My Andersson; Nihan Çarçak (Cells)
Epilepsy is a chronic neurological disorder marked by recurrent seizures, significantly impacting individuals worldwide. Current treatments are often ineffective for a third of patients and can cause severe side effects, necessitating new therapeutic approaches. Glial cells, particularly astrocytes, microglia, and oligodendrocytes, are emerging as crucial targets in epilepsy management. Astrocytes regulate neuronal homeostasis, excitability, and synaptic plasticity, playing key roles in maintaining the blood–brain barrier (BBB) and mediating neuroinflammatory responses. Dysregulated astrocyte functions, such as reactive astrogliosis, can lead to abnormal neuronal activity and seizure generation. They release gliotransmitters, cytokines, and chemokines that may exacerbate or mitigate seizures. Microglia, the innate immune cells of the CNS, contribute to neuroinflammation, glutamate excitotoxicity, and the balance between excitatory and inhibitory neurotransmission, underscoring their dual role in seizure promotion and protection. Meanwhile, oligodendrocytes, primarily involved in myelination, also modulate axonal excitability and contribute to the neuron–glia network underlying seizure pathogenesis. Understanding the dynamic interactions of glial cells with neurons provides promising avenues for novel epilepsy therapies. Targeting these cells may lead to improved seizure control and better clinical outcomes, offering hope for patients with refractory epilepsy.